2014
DOI: 10.21664/2238-8869.2014v3i2.p180-210
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização dos Solos e da Estrutura Fitossociológica da Vegetação de Veredas da Chapada no Triângulo Mineiro

Abstract: As veredas se destacam como um sistema de drenagem superficial composto pela rede de drenagem com cursos d’água que ocupa os interflúvios largos dentro do domínio Cerrado. Nas Veredas os solos são formados sob condições de drenagem deficiente. Nestas condições há uma tendência para a formação de solos hidromórficos. Com o objetivo de investigar a importância e o uso dado para os recursos naturais das veredas pela população rural do município de Uberlândia-MG foram realizadas entrevistas com 20 proprietários ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
0
8
0
8
Order By: Relevance
“…Th e families with the largest number of species were Poaceae (n = 53), Cyperaceae (n = 44), Asteraceae (n = 24), Eriocaulaceae (n = 18), Xyridaceae (n = 17), Lentibulariaceae (n = 16), Melastomataceae (n = 12), Rubiaceae (n = 12) and Fabaceae (n = 11), collectively accounting for 71.9% of the sampled angiosperms. In the studies conducted by Araújo et al (2002), Guimarães et al (2002), Ramos (2004), and Oliveira et al (2009), these same families, with the exception of Lentibulariaceae, also showed the highest species richness. Guimarães et al (2002) registered no Lentibulariaceae species and only three Xyridaceae species.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…Th e families with the largest number of species were Poaceae (n = 53), Cyperaceae (n = 44), Asteraceae (n = 24), Eriocaulaceae (n = 18), Xyridaceae (n = 17), Lentibulariaceae (n = 16), Melastomataceae (n = 12), Rubiaceae (n = 12) and Fabaceae (n = 11), collectively accounting for 71.9% of the sampled angiosperms. In the studies conducted by Araújo et al (2002), Guimarães et al (2002), Ramos (2004), and Oliveira et al (2009), these same families, with the exception of Lentibulariaceae, also showed the highest species richness. Guimarães et al (2002) registered no Lentibulariaceae species and only three Xyridaceae species.…”
Section: Resultsmentioning
confidence: 82%
“…In the studies conducted by Araújo et al (2002), Guimarães et al (2002), Ramos (2004), andOliveira et al (2009), these same families, with the exception of Lentibulariaceae, also showed the highest species richness. Guimarães et al (2002) registered no Lentibulariaceae species and only three Xyridaceae species.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations